PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA PEGAWAI DI INSTANSI PEMERINTAH DAERAH - Fahrel Alfais. A; Herlina; Syafwandi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the influence of organizational culture on organizational commitment and employee performance in local government agencies. Organizational culture is one of the essential elements that shape individual behavior within an organization. Organizational commitment reflects the level of attachment and loyalty of employees to the organization where they work, while employee performance refers to the achievement of work results according to predetermined standards. This research uses a quantitative approach with a survey method by distributing questionnaires to several employees in local government institutions. The results showed that organizational culture positively and significantly affects organizational commitment and employee performance. A strong organizational culture can create a conducive work atmosphere, increase work morale, and foster employee loyalty to the organization. Therefore, improving organizational culture is one of the strategies that can be applied by local government institutions to improve the performance of civil servants.